Competition and regulation in the Finnish ATM industry - Tuomas Markkula; Tuomas Takalo (Bank of Finland, 2021)
Declining ATM numbers pose a challenge for competition policy and financial regulatory authorities. In this report we review the Finnish experience of regulating the competition in the ATM industry. To analyze the Finnish developments we extend the model of Kopsakangas-Savolainen and Takalo (2014), and draw on the existing literature and benchmarks from the selected other countries. We document how changes in the ATM market regulation and market structure has decoupled the ATM network size from the declining cash use in Finland. The Finnish regulation has almost exclusively focused on foreign fees, while in general it would be better to regulate interchange fees. If the optimal fee regulation is not feasible, the authorities could also consider quantity regulation.
urn:nbn:fi:bof-202110142058
Keywords: 330; ATM industry; cash; competition policy; optimal regulation; retail payments